2013
DOI: 10.1111/cogs.12041
|View full text |Cite
|
Sign up to set email alerts
|

Object Orientation Affects Spatial Language Comprehension

Abstract: Typical spatial descriptions, such as "The car is in front of the house," describe the position of a located object (LO; e.g., the car) in space relative to a reference object (RO) whose location is known (e.g., the house). The orientation of the RO affects spatial language comprehension via the reference frame selection process. However, the effects of the LO's orientation on spatial language have not received great attention. This study explores whether the pure geometric information of the LO (e.g., its ori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
15
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 53 publications
7
15
0
Order By: Relevance
“…Past research has focused on the production and comprehension of spatial terms (e.g., Burigo & Sacchi, 2013;Carlson & van Deman, 2008;Carlson-Radvansky & Irwin, 1994;Carlson-Radvansky & Logan, 1997;Coventry & Garrod, 2004;Lipinski, Schneegans, Sandamirskaya, Spencer, & Sch€ oner, 2011;Logan, 1995Logan, , 1996Regier & Carlson, 2001). A critical representation related to conflict and selection in spatial term use is a spatial reference frame.…”
Section: Conflict and Selection In Spatial Term Usementioning
confidence: 99%
“…Past research has focused on the production and comprehension of spatial terms (e.g., Burigo & Sacchi, 2013;Carlson & van Deman, 2008;Carlson-Radvansky & Irwin, 1994;Carlson-Radvansky & Logan, 1997;Coventry & Garrod, 2004;Lipinski, Schneegans, Sandamirskaya, Spencer, & Sch€ oner, 2011;Logan, 1995Logan, , 1996Regier & Carlson, 2001). A critical representation related to conflict and selection in spatial term use is a spatial reference frame.…”
Section: Conflict and Selection In Spatial Term Usementioning
confidence: 99%
“…Such configural cues include global features concerning the environment's geometry and symmetry (Shelton and McNamara, 2001;Tverksy, 1981), its salient axes (e.g., those formed by prominent streets, Werner & Schmidt, 1999), and the slope of its terrain (Nardi et al, 2012;Weisberg & Newcombe, 2014), among many more. Beyond such global configural cues, relevant information about how to interact with the world also comes from more local configural cues, such as the direction and orientation of objects in the environment (e.g., Burigo & Sacchi, 2013), the internal elongated axes of the objects (Quinlan & Humphreys, 1993;Sekuler & Swimmer, 2000), and the affordances of those objects (Gibson, 1979;Costantini et al, 2010). Importantly, as social animals, we also use cues about the location and orientation of others in space to guide our language use and actions (e.g., Galati et al, 2013;Özyürek, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the petrol canister data used in this work cannot be captured from the AVS model or any of its extensions, presumably because of the lack of an appropriate trajector representation (see also the discussion in Hörberg (2008)). Furthermore, Burigo and Sacchi (2013) showed that pure geometric properties of the trajector also a ect spatial language apprehension. Coventry et al (2010) conducted a study in which they tracked eye movements of people during the apprehension of spatial terms.…”
Section: Resultsmentioning
confidence: 99%